Application of Advanced Characterization Techniques to SmartSiC™ Product for Substrate-Level Device Performance Optimization - Zielinski, Marcin; Cela, Enrica; Radisson, Damien; Chapelle, Audrey; Schwarzenbach, Walter; Guiot, Eric; Simon, Roland B.; Drouin, Alexis; Biard, Hugo (Materials science forum, 2024)
A review of the specific characterisation techniques developed and customized for SmartSiC™ substrates is given. A focus is made on thermal characterization of this engineered structure as well as its beneficial features with regards to bipolar degradation.